Гидродинамическое совершенствование проточных частей осевых гидротурбин при помощи пространственного профилирования лопастей рабочих колес - Русанов, Андрей Викторович; Хорев, Олег Николаевич; Рябова, Светлана Александровна; Косьянов, Дмитрий Юрьевич; Сухоребрый, Петр Николаевич (НТУ "ХПИ", 2016)
Представлены результаты численного исследования влияния пространственного профилирования лопастей рабочего колеса осевой гидротурбины при помощи сложных окружных, осевых и комбинированных навалов на характеристики потока в проточной части. Проведен анализ структуры потока в элементах проточной части, приведены зависимости значения мощности и КПД от величины окружных и осевых навалов при оптимальном режиме работы. Исследования потока выполнены при помощи программного комплекса IPMFlow.

The results of the numerical investigations influence of spatial runner blade profiling in Kaplan turbine by means of the complex circular, axial and combined offsets upon flow characteristics in flow part are presented. The analysis of flow pattern in the flow part elements has been conducted; dependences of capacity and efficiency on circular and axial offset values at optimum operating conditions are shown. The comparison of the energy characteristics of the flow part with the original runner and upgraded one by means of combined offset at optimum operating condition is presented. The flow investigations have been carried out using the software system IPMFlow.
Hydrodynamic improvement of flow parts of Kaplan turbines by means of the spatial profiling of the runners blades
Keywords: окружной навал лопасти; осевой навал лопасти; ПЧ; КПД; отсасывающая труба; ГЭС; circular offsets; axial offsets